Desiccation, postharvest maturity and seed aging of tall oat-grass - Stanisavljević, Rede; Djokić, Dragoslav; Milenković, Jasmina; Terzić, Dragan; Djukanović, Lana; Stevović, Vladeta; Dodig, Dejan (Pesquisa Agropecuaria Brasileira, 2011)
The objectives of this work were to determine whether and at which seed physiological maturity stage the diquat desiccant affects the tall oat-grass (Arrhenatherum elatius) seed quality and yield, as well as the proper storage period between harvest and sowing. Diquat desiccation was evaluated in applications during milk or dough seed maturation stages. Seeds conventionally produced and stored under traditional storage conditions were used for the analyses. Seed samples were drawn every 30th day after harvest (DAH). After the 240th DAH, samples were drawn every 90th day up the to 690th DAH. The highest yield were obtained by desiccation applied at the beginning of the seed dough stage, with a satisfactory seed quality. Both final germination and seedling growth parameters achieved their maximum values between 180th and 240th DAH. Oat-grass seeds preserved satisfactory level of final germination (75%) up to 420th DAH. The application of diquat desiccant at the beginning of seed dough maturity stage can be a good solution for seed production of tall oat-grass. Early spring is the best sowing period for freshly harvested seeds of tall oat-grass regarding germination and seedling growth.